Characteristics and comorbidity of confirmed COVID-19 death cases at the Arifin Achmad Hospital in Riau province from March 2020 to September 2021 - Musfardi Rustam; Martha Hasanah Rustam; Afrinaldy Rustam; Yepi Kurniadi; Imam Slamet Prasetio; Umi Nadatul Annisa (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the characteristics and comorbidity among those who died due to coronavirus disease-2019. Method: The cohort retrospective study was conducted at Arifin Achmad Public Hospital, Riau, Indonesia, from January 5 to February 28, 2022, and comprised data of all coronavirus disease-2019 patients who had been treated at the hospital from March 2020 to October 2021. Data was analysed using SPSS version 20. Logistic regression including univariate and bivariate analysis was applied. Results: Of the 1,694 patients, 916(54.1%) were females and 904(53.4%) were aged >50 years. The most frequent comorbidity was type 2 diabetes mellitus 280(16.5%), followed by hypertension 254(14.9%) and chronic renal failure 194(11.4%). Mortality was significantly higher among those aged >50 years and those having diabetes mellitus and hypertension (p<0.05). Conclusion: Patients with comorbidities were at a greater risk of acquiring coronavirus disease-2019 infection. Keywords: Diabetes Mellitus, Comorbidity, Hypertension, Kidney Failure, Chronic, COVID-19.